Phytochemical Study And Evaluation Of The Antimicrobial And Antioxidant Activity Of Essential Oils And Phenolic Compounds Of Pistacia Lentiscus L - Arab, K.; Bouchenak, O.; Yahiaoui, K. (University of Eloued جامعة الوادي, 2014)
This work aims for the phytochemical study and evaluation of the antioxidant activity of phenolic compounds and essential oils of medicinal plant Pistacia lentiscus L. quantitatively and qualitatively. Through the results obtained, it appears that the leaves and fruits are rich in substances with a high antioxidant power. The yield of the phenolic compounds obtained from 10g to powder of plant is for leaves 116.49 % and 61.34 % for fruit . For essential oils, it is 0.253 ± 0.131 % for 100 g of plant material. The chromatographic profile of the essential oil of Pistacia lentiscus L. shows that monoterpenes are the major compound (9.675 % of identified molecules). The strong antioxidant activity of extracts obtained only confirms the traditional use of this plant by the local population.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 01
Keywords: chromatographic profile ; monoterpenes , secondary metabolites ; Boumerdes.